KINERJA PEMERINTAH DESA DALAM PROGRAM DESA BERSIH NARKOBA (BERSINAR) DI DESA SEBERANG TALUK KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Nurul Mardhiyah; RFS, Harapan Tua (Pusat Riset dan Inovasi Nasional, 2022)
Drug abuse has become a complex problem faced by Indonesia and of course requires a special strategy and the active role of all parties in its prevention and handling. This is evidenced by the rampant cases of drug trafficking and abuse that occur in villages in Kuantan Singingi, one of which is Seberang Taluk Village, Central Kuantan District. This study aims to see the performance of the Village Government in the Clean Drugs (Bersinar) Village program in Seberang Taluk Village, Central Kuantan District, Kuantan Singingi Regency. In this study, the authors used descriptive qualitative research methods. The researcher uses Dwiyanto's theory where the indicators used in measuring organizational performance use 4 (four) indicators, namely, productivity, responsiveness, responsibility, and accountability. The results of this study indicate that the distribution and abuse of drugs in Seberang Taluk Village has decreased during the program of the Clean Drugs Village (Bersinar) with a percentage of approximately 80%. However, the implementation of the Shining Village Program still faces several obstacles. Researchers found factors that influence the implementation of this program, which include the problem of limited budget, incompetent human resources, and lack of public self-awareness. Overall, the Seberang Taluk Village Government, Central Kuantan District can be said to have been quite good at implementing the Shining Village program in preventing drug trafficking.